New insights into audiovisual translation and media accessibility - Díaz-Cintas, Jorge; Matamala, Anna, 1973-; Neves, Josélia (Approaches to translation studies, 2010)
This volume aims to take the pulse of the changes taking place in the thriving field of Audiovisual Translation and to offer new insights into both theoretical and practical issues. Academics and practitioners of proven international reputation are given.